The effect of Ulva lactuca on in vitro ruminal gas production kinetics, intrinsic methane production and the performance of Dohne Merino ewes - Nell, Sone (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.